Endoscopic septomucoplasty in telangiectasia using buccal mucosa graft : an alternative technique - Salina Husain; Gendeh BS (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Epistaxis is one of the common presenting symptoms of patients with hereditary haemorrhagic telangiectasia (HHT). Majority of patients required blood transfusion due to intractable nasal bleeding. Septodermoplasty is an effective treatment for HHT, however it gives rise to persistent nasal crusting and foul smelling nasal discharge post surgery. We present an endoscopic septomucoplasty using buccal mucosa graft as an alternative technique to septodermoplasty.